\(\displaystyle{5}{\left\lbrace{\left[{4}{\left({q}–{4}\right)}+{18}\right]}–{\left[{2}{\left({5}{q}–{2}\right)}+{3}\right]}\right\rbrace}=\)

\(\displaystyle={5}{\left\lbrace{\left[{4}{q}–{16}+{18}\right]}–{\left[{10}{q}–{4}+{3}\right]}\right\rbrace}=\)

\(\displaystyle={5}{\left\lbrace{4}{q}+{2}–{10}{q}–{1}\right\rbrace}=\)

\(\displaystyle={5}{\left\lbrace{1}–{6}{q}\right\rbrace}=\)

\(\displaystyle={5}{\left({1}–{6}{q}\right)}\)

\(\displaystyle={5}{\left\lbrace{\left[{4}{q}–{16}+{18}\right]}–{\left[{10}{q}–{4}+{3}\right]}\right\rbrace}=\)

\(\displaystyle={5}{\left\lbrace{4}{q}+{2}–{10}{q}–{1}\right\rbrace}=\)

\(\displaystyle={5}{\left\lbrace{1}–{6}{q}\right\rbrace}=\)

\(\displaystyle={5}{\left({1}–{6}{q}\right)}\)